(3fJGFL KeQGJ eYGQa GdCagGe hLhOI GdCPgGf aj EjVGM hJHjjf eG UM ESfGOg dSjOfG YHO Gddg Hf YHGS QVj Gddg Yfgs - (3GdWQjfj, GdeGdcj, YHO GdLhGO Hf EHQGgje, (B1073 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3bO Od GdcJGH hGdSfI hGdBKGQ hGdefbhd hGdeYbhd Ydi aVd hNjQ cKjQ YXje dCQHGH GdCagGe eeG dG ojMUi cKQI hdh Hage GdHYV ef GdCMcGe (B...s
(3BNQgG (B:s
... (3hCf jbGd gh ZHj dG jYQa aef Mbb faSg HgPg GdCefjI XgQ aj bdHg GdCSQGQ GdEdGgjI hGdeYGQa GdUeOGfjI hgPG BNQ eG jSQ dfG (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2/50s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdMOjK hGdeUWdMs